Interjections Functioned as Pragmatic Markers and Given/ New Information - Maya Lisa Aryanti (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
The purposes of this research are to find out the functions of the interjections functioned as pragmatic markers and what they indicate to, to find out which information the interjections denote and to find out how many functions the interjections functioned as pragmatic markers possibly have. The data are five different interjections taken from five different novels. The results of this research are concerning to the functions of the interjections functioned as pragmatic markers. Generally, the functions are utterance initial, attention marker and a response signal. Further, interjections functioned as pragmatic markers take form as attitude, feelings or both.  The interjections denote given/old information, new information and both.  The last result is that it is possible for interjections to have more than one function. To sum up, interjections functioned as pragmatic markers have roles and forms  in discourses. In addition, interjections functioned as pragmatic markers denote information.